1984
DOI: 10.1029/tc003i002p00157
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic results from the Central Sierra Nevada: Constraints on reconstructions of the western United States

Abstract: Paleomagnetic results from three plutons of the central Sierra Nevada limit the motion of the Sierra Nevada relative to the North American craton to 5° ± 8° of poleward motion and 7° ± 11° of clockwise rotation since about 90 Ma. The indicated rotation and translation are not significant at the 95% confidence level. A new tectonic model is presented that is consistent with all available paleomagnetic data from the Sierra Nevada, Great Valley, Klamaths, Oregon Coast Range, Cascades, and western Nevada. The pale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Evidently some plate-margin units are relatively uncomplicated and internally undeformed, but others have suspiciously large elongations. In Figure 11 Figure 13b shows the VGP distribution for the Grace Meadow pluton (SNY2) of the Yosemite Valley area [Frei et al, 1984]. This distribution also is elongate, in the same general sense as seen in Figure 13a.…”
Section: Cratonmentioning
confidence: 57%
“…Evidently some plate-margin units are relatively uncomplicated and internally undeformed, but others have suspiciously large elongations. In Figure 11 Figure 13b shows the VGP distribution for the Grace Meadow pluton (SNY2) of the Yosemite Valley area [Frei et al, 1984]. This distribution also is elongate, in the same general sense as seen in Figure 13a.…”
Section: Cratonmentioning
confidence: 57%
“…Early work by GrommC andMerril (1965) andGrommC et al (1967) on plutons from the Sierra Nevada gave results that were generally consistent with those from cratonic North America. Recent detailed demagnetization studies by Frei et al (1984) of three plutons from the central Sierra Nevada showed a displacement of 8 2 10" from the south. Although the displacement is not significant at the 95% probability level, there is nevertheless a bias toward shallow inclinations, and a small poleward displacement of lower probability is indicated.…”
Section: Tectonic Implicationsmentioning
confidence: 98%
“…Sources: 1) Magill et al (1982); 2) Sheriff (1984); 3) Wells et al (1989); 4) compilation of Gromme et al (1986); 5) Beck et al (1986); 6) compilation in Frei et al (1984), revised using N. Am. Cretaceous reference pole of Globerman and Irving (1988) (plat 71 N; plon 196 E; A95 = 4.9).…”
Section: Block Modelmentioning
confidence: 99%